Review on the Removal of Metal Ions from Effluents Using Seaweeds, Alginate Derivatives and Other Sorbents - Fiset, Jean-François; Blais, Jean-François; Riveros, Patricio (Revue des sciences de l'eau / Journal of Water Science, 2008)
AbstractBiosorbents, especially those derived from seaweed (macroscopic algae) and alginate derivatives, exhibit high affinity for many metal ions. Because biosorbents are widely abundant (usually biodegradable) and less expensive than industrial synthetic adsorbents, they hold great potential for the removal of toxic metals from industrial effluents. Various studies have demonstrated the efficiency of living and non-living micro-organisms, such as bacteria, yeasts, moulds, micro-algae, cyanobacteria and biomass from water treatment sewage to remove metals from solution. Several types of organic and inorganic biomass have also been used as sorbent materials. In addition, by-products from the forestry industry, as well as agriculture waste and natural sorbents, have also been studied. This paper reviews and summarizes some key recent developments in these areas and it describes and discusses some specific applications of selected natural sorbents.